"Vitamin D supplementation and COVID-19 treatment: A systematic review and meta-analysis". Issue 4 (July 2021) - Rawat, Dimple; Roy, Avishek; Maitra, Souvik; Shankar, Vivek; Khanna, Puneet; Baidya, Dalim Kumar
Abstract: Background: Vitamin-D is an immune-modulator which might be linked to disease severity by SARS-CoV-2. Methods: Meta-analysis of RCTs and quasi-experimental studies, evaluating the role of vitamin-D supplementation in COVID patients was done. Results: Total 5 studies (3 RCTs and 2 Quasi-experimental) including n = 467 patients were included. Vitamin D didn't reduce mortality (RR 0.55, 95%CI 0.22 to 1.39, p = 0.21), ICU admission rates (RR 0.20, 95% CI 0.01–4.26, p = 0.3) and need for invasive ventilation (RR 0.24, 95% CI 0.01–7.89, p = 0.42). Conclusion: No significant difference with vitamin-D supplementation on major health related outcomes in COVID-19. Well-designed RCTs are required addressing this topic. Highlights: Efficacy of vitamin-D in patients with COVID-19 is controversial. Previous RCTs demonstrated contrasting results. The meta-analysis did not show any outcome benefit with vitamin D supplementation with low certainty of evidence.